2008
DOI: 10.1111/j.1600-0447.2008.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of peer support groups in psychosis: a randomized controlled trial

Abstract: Objective:  To investigate the effect of a (minimally) guided peer support group (GPSG) for people with psychosis on social network, social support, self‐efficacy, self‐esteem, and quality of life, and to evaluate the intervention and its economic consequences. Method:  In a multi‐center randomized controlled trial with 56 patients in the peer support group and 50 patients in the control condition, patients were assessed at baseline and after the last meeting at 8 months. Results:  The experimental group showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 26 publications
4
140
1
5
Order By: Relevance
“…Intervention adherence can have a substantial impact on the effectiveness of interventions, as demonstrated by the clinical results of this study (Castelein et al 2008a). The sensitivity analysis specifically focused on the economic consequences of intervention adherence in the peer support groups.…”
Section: Sensitivity Analysismentioning
confidence: 57%
See 4 more Smart Citations
“…Intervention adherence can have a substantial impact on the effectiveness of interventions, as demonstrated by the clinical results of this study (Castelein et al 2008a). The sensitivity analysis specifically focused on the economic consequences of intervention adherence in the peer support groups.…”
Section: Sensitivity Analysismentioning
confidence: 57%
“…Although the number of included patients was in accordance with required sample sizes calculated prior to the study, relevant differences between study groups could not be found on the WHOQoL-Bref. However, additional outcome measures did show improved functioning on various domains that are relevant for patients with psychosis (Castelein et al 2008a). For instance, patients in the peer support groups had a significant increase in contacts with peers outside of the sessions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations